Ratsional ovqatlanishni tashkil etish (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
Nutrition is one of the important factors that have a significant impact on health status, labor and influence of the external environment. It is said that Hippocrates said, "Rational meals must be food and medicine. The normal growth, development, healthy, and obesity to prevent diseases, Heart-viticulture, diabetes, high blood pressure and cancer shall be prevented